Value chain and Multicrop baseline of TAFS-WCA: Case of Democratic Republic of Congo (DRC) - Arouna, A.; Yergo, W.G.; Aboudou, R.; Ouedraogo, M.; Abdoulaye, T. (2023)
This report presents the results of the baseline survey of the Transforming Agrifood Systems in West and Central Africa (TAFS-WCA) initiative in DRC. Three regions of DRC were surveyed. Data were collected using a smart tablet with the CSPro application. A total of 1,024 actors in agricultural production and value chain were surveyed during the baseline data collection in DRC. Actors involved in the baseline data collection are producers of rice, maize, soybean, beans, cassava, sweet potato, inputs dealer, traders, processors and service providers. All data analyses were carried out with the STATA 16 software.